Concentration-dependent effect of bleaching agents on the immunolabelling of interleukin-6, interleukin-17 and CD5-positive cells in the dental pulp - Benetti, F. [UNESP]; Gomes-Filho, J. E. [UNESP]; Ferreira, L. L. [UNESP]; Sivieri-Araújo, G. [UNESP]; Ervolino, E. [UNESP]; Briso, A. L.F. [UNESP]; Cintra, L. T.A. [UNESP] (Wiley, 2018)
Aim: To evaluate lymphocyte-like cell activation (CD5-positive cells) and the expression of interleukin (IL)-6 and IL-17 in the pulp after tooth bleaching with two concentrations of hydrogen peroxide (H2O2). Methodology: The right and left maxillary molars from 40 rats were treated randomly with bleaching gel with 20% H2O2 (BLUE group, 1 application of 50 min), 35% H2O2 (MAXX group, three applications of 15 min), or placebo gel (control). After 2 and 30 days, the rats were killed (n = 10), and the jaws were processed for histological and immunohistochemistry analysis of the pulp tissue. The scores of inflammation and immunolabelling (IL-6/IL-17) were submitted to Mann–Whitney and Kruskal–Wallis followed Dunn tests, respectively; anova tests were used for comparisons of number of CD5-positive cells and pulp chamber area values (P < 0.05). Results: At 2 days, 60% of specimens of the BLUE group were associated with moderate inflammation in pulp horns, and in the MAXX group with necrosis (P < 0.05). At 30 days, the pulp was organized, and tertiary dentine was formed. The MAXX group had superior immunolabelling of IL-17 at 2 days differing significantly from other groups (P < 0.05). At 2 days, 90% of the specimens of the BLUE group had moderate immunolabelling of IL-6, and 50% of the MAXX group had severe immunolabelling, both significantly different from the control (P < 0.05). There was no significant difference between the groups at 30 days (P > 0.05). CD5-positive cells were present at 2 and 30 days, particularly in the bleached groups (P < 0.05), without significant difference between time periods (P > 0.05). Conclusions: IL-6 and IL-17 participated in inflammation in the pulp tissue of rats after tooth bleaching, particularly at 2 days. The immunolabelling was greater with increasing H2O2 concentration. This process was accompanied by the prolonged activation of CD5-positive cells.
Keywords: CD5; dental pulp; hydrogen peroxide; interleukin-17; interleukin-6; tooth bleaching